The Transformative Roles of Cooperative Learning in Promoting EFL Students' Writing Competence - Sudirman, Anselmus; Fifardin, Ferdinandus; Berkanis, Maria Imelda (Edu-Ling: Journal of English Education and Linguistics, 2023)
Cooperative learning is primarily aligned with the transformative roles that it can play in responding to EFL students' writing skills. This review article investigates the personal, relational, educational, institutional, and global aspects of cooperative learning transformatively. Personal efforts to improve writing skills highlight the relevance of diverse small-scale teamwork. Individual student efforts are the gold standard for adopting coordination and teamwork. More significantly, students want to regain self-confidence by adopting socio-emotional skills that improve their collaboration and involvement. It also maintains a positive attitude and a sense of pride in the face of institutional transformation. The main reason is that institutional policy, which heavily encourages writing competence, attempts to help students develop and update their knowledge, communication, creativity, responsibility, and competence capacities. As a result, transformative learning brings together the strengths of small-scale personal, relational, educational, and institutional activities to develop networked relationships in academic communities. Furthermore, cooperative learning functions well in writing contexts to assist students in accepting democratic ideals, attitudes, and principles. Cooperative learning thus plays transformative roles while enhancing students' writing competence in global contexts to re-articulate ideas that transformational values arise through in-class writing activities that contribute to global cooperative learning. Keywords: Cooperative learning, Transformative Role, Writing Competence, EFL writing